Planned load reduction strategies to maintain optimal repetitions for hypertrophy training in leg press for women - Machado, Danilo S.; Koch, Alexander J.; Machado, Marco (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. According to the ACSM’s position stand on resistance training, there is strong evidence (category A) that the optimal number of repetitions to optimize hypertrophy should be between 8 and 12 repetitions per set for each exercise. Aim of Study. We investigated which intensity scheme would maintain 8-12 repetitions during repeated sets of resistance exercise performed until muscular failure. Material and Methods. Twenty-eight resistance-trained women (age = 26.1 ± 6.6 years, body mass = 66.2 ± 5.94 kg, height = 165 ± 6 cm) were tested over a five-week period. In week 1 the subjects were tested for 10RM leg press. In weeks 2-5 the subjects completed four sets of leg presses performed until muscular failure, with 60 s inter-set rest intervals in a randomized, counterbalanced order. Set 1 of each bout was performed at 10RM, with differing intensity for sets 2-4 as follows: (CON) 10RM load for all sets, (RED5) 5% load reduction after each set, (RED10) 10% load reduction after each set, and (RED15) 15% load reduction after each set. Results. The number of repetitions completed differed (p < 0.001) depending on the conditions. Repetitions were reduced below set 1 in sets 2-4 under CON (p < 0.05) and for sets 3-4 (p < 0.05) in RED5. RED10 and RED15 resulted in increased repetitions during sets 2-4 (p 60%) of sets in the range of 8-12 repetitions, where both CON and RED15 resulted in <50% of sets in the range of 8-12 repetitions. Time under tension (TUT) was kept within a 20-70 s per set window for most sets (95% CI) for RED10 and RED15. Conclusions. Load reductions of 5-10% in subsequent sets should allow for the maintenance of 8-12 repetitions for most sets of resistance exercise, with load reductions of 10% more likely to maintain optimal TUT.
Keywords: resistance training; volume; intensity; hypertrophy